A Bibliometric and Topic Modeling Overview of Kajian Malaysia between 2011 and 2020: A Research Note - Mohd Faiz Hilmi,; Yanti Mustapha, (Kajian Malaysia, 2022)
Kajian Malaysia, published by Penerbit Universiti Sains Malaysia, is an interdisciplinary journal which provides a forum for a broad range of social sciences and humanities research. This research note presents a bibliometric review of the articles published in the journal Kajian Malaysia between 2011 and 2020. The purpose of this research note is to evaluate publication patterns and the topic model of articles published in Kajian Malaysia. The bibliographical material applied in this study was retrieved from the Scopus database. This study bibliometrically examines 192 documents published in Kajian Malaysia from 2011 to 2020 to rank the most productive countries, institutions, authors, keywords, influential articles and the topic model. This research note assists researchers with an understanding of the development of Kajian Malaysia, provides an important reference for Kajian Malaysia’s future trajectory as well as provides an effective method of analysis for the future evaluation of journals.